ANALYSIS OF SEDIMENT TEXTURE AND ORGANIC CARBON CONTENT ON MACROZOOBENTHOS ABUNDANCE IN THE MANGROVE AREA OF KARANGTALUN NORTH CILACAP - Dewi Wisudyanti Budi Hastuti; Riviani Riviani; Anandita Ekasanti; Emyliana Listiowati; Dewi Nugrayani; Ririn Dwi Avrila; Davy Ananda Catur Wibowo (Jurnal Perikanan Unram, 2024)
Mangrove forests have an important role in reducing the impact of global warming as a place to absorb carbon dioxide (CO2) from the atmosphere which is mostly stored in sediment. Mangroves are a good habitat for aquatic biota such as macrozoobenthos. Macrozoobenthos are organisms that inhabit the bottom of sea waters and also exist in stable sediments. The aim of this research is to determine sediment texture, sediment organic carbon content, macrozoobenthos abundance and the relationship between sediment type and macrozoobenthos abundance. The method used in sampling was purposive sampling with a total of 3 stations. Sediment samples were taken using a core sampler at depths of 0-10 cm, 10-20 cm and 20-30 cm, while macrozoobenthos samples were taken using the hand sorting method. Organic carbon content was analyzed using the Loss on Ignition (LOI) method. The research results showed that the macrozoobenthos community structure at all stations produced low diversity and dominance indices and high uniformity indices.   The type of sediment texture in the research area shows an average value of the sediment fraction of 4.43% sand, 71.11% dust and 24.45% clay. The highest organic carbon content was found at stations near brackish water areas with an average of 12.06%, while stations near factory areas had the lowest content at 5.89%. There is a strong relationship between the type of sediment texture and the abundance of macrozoobenthos in the Karangtalun mangrove area, North Cilacap.